2022
DOI: 10.3390/ijms231911205
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Low Bone Mineral Density in C57BL/6 Mice Is Reflective of Aberrant Bone Morphogenetic Protein-2 Signaling Observed in Human Patients Diagnosed with Osteoporosis

Abstract: Osteoporosis (OP) is a bone disorder characterized by decreased bone mineral density (BMD). Bone Morphogenetic Protein-2 (BMP-2) injections are used to promote bone formation in OP patients. However, patients are unresponsive to BMP-2 while displaying an upregulation of BMP Receptor Type 1a (BMPRIa) and protein kinase CK2α (CK2α). A synthetically produced peptide named casein kinase 2.3 (CK2.3) utilizes the BMP-signaling pathway as it enhances osteogenesis of primary osteoblasts isolated from OP patients, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 69 publications
0
1
0
Order By: Relevance
“…To ensure B6 mice are a reliable model to investigate aberrant BMP-signaling, the expression of BMPRIa must be further established. We first confirmed that the BMSCs of US 15-month B6 mice overexpress BMPRIa compared to US 6-month mice via western blotting and confocal microscopy, confirming previous data (Figure 1) [67,81]. This overexpression may be caused by aberrant BMPsignaling, and the cells are compensating for the lack of signaling and thereby upregulating BMPRIa expression.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…To ensure B6 mice are a reliable model to investigate aberrant BMP-signaling, the expression of BMPRIa must be further established. We first confirmed that the BMSCs of US 15-month B6 mice overexpress BMPRIa compared to US 6-month mice via western blotting and confocal microscopy, confirming previous data (Figure 1) [67,81]. This overexpression may be caused by aberrant BMPsignaling, and the cells are compensating for the lack of signaling and thereby upregulating BMPRIa expression.…”
Section: Discussionsupporting
confidence: 88%
“…It was recently demonstrated that primary osteoblasts isolated from OP patients overexpress BMPRIa compared to control patients via immunofluorescent staining and western blotting [67]. Additionally, this overexpression of BMPRIa is also observed in the BMSCs isolated from 15-month mice compared to 6-month mice as illustrated by confocal microscopy [81]. However, the total protein concentration of BMPRIa from whole cell lysates has never been determined and should be explored to confirm this overexpression.…”
Section: -Month B6 Mice Overexpress Bmpria Compared To 6-month Mice V...mentioning
confidence: 99%
See 1 more Smart Citation
“…In 6-to-9-day-old C57BL/6J mice injected with CK2.3 via the calvaria and 8-week-old mice injected via the tail vein, mice showed increased bone formation and increased bone mineral density. At the same time, osteoclast activity appeared to be suppressed, indicating CK2.3 has the potential to alleviate the symptoms of OP by simultaneously enhancing osteoblast activity and inhibiting osteoclast activity, inducing bone growth and repair [174][175][176]. The principle of design of BMPRIa biomimetic peptides CK2.1 and CK2.3 and their effects are summarized in Figure 3.…”
Section: Targeting Ck2 Interactions With Its Substrates-novel Approachmentioning
confidence: 99%